Determination of indoor radon gas levels in some buildings constructed with Ahlat stone in Ahlat/Bitlis - Kuluozturk, M. F.; Buyuksarac, A.; Ozbey, F.; Yalcin, S.; Dogru, M. (Springer, 2019)
Ahlat stone that is commonly used country wide specially Bitlis and neighbour cities is a volcanic stone (andesitic tuff) with a porous structure. Radon gas levels were determined in buildings constructed with Ahlat stone and concrete by using CR-39 passive detectors. Additionally, radon gas levels in tap waters of the some buildings were also detected by using active radon detection system. The radon gas level results were compared with smoking habit of household, ventilation periods and reasons of death if there are.
4th International Conference on Computational and Experimental Science and Engineering (ICCESEN) -- OCT 04-08, 2017 -- Kemer, TURKEY
Keywords: Ahlat stone; Radon gas levels; CR-39; Indoor radon